Optimal design of sedimentation tanks for effluent of marble works and use of settled solids in concrete - Unlu, A; Urgup, MN; Hasar, H (Taylor & Francis Ltd, 2003)
The aims of this study are to determine the settling characteristics of wastewater from the marble works in Elazig-City province experimentally and to optimise the dimensions of the sedimentation basins. The results can be directly used in small plants. Quiescent settling experiments were carried out at constant temperature for retention times of 0.5 to 2 hours by taking composite samples of two hours. The results obtained from through frequency distribution curves have shown that the settling was of a discrete type. The relationship between the hydraulic loading and the efficiency curves was obtained and thus the efficiency value of basins at different surface areas was determined. The dimensions of the basins for minimum turbulence, stable flow without bottom drift and maximum settling efficiency were investigated. The Froud Number that expresses the flow stability, the Reynolds Number that indicates the turbulence effect, and the horizontal velocities at basins were considered as limiting factors, while the surface areas of basins were held constant. The basin 9, with surface area of 80 m 2 (4 mx20 m), is the most suitable one with efficiency of 99.5%. Basin 7, with surface area of 45 m 2 (3 mx15 m), where the efficiency could be increased by building an entry region, is the most economic one according to construction. The use of settled solids at the bottom of basin within concrete classes C14 and C20 was experimentally investigated through compression tests. The compression strength of cube samples adulterated with the settled solids for both concrete classes of C14 and C20 were 3-4% better than the cube samples with normal aggregate.
Keywords: sedimentation; discrete settling; recycling; concrete; marble plants